Adaptation of the Coping With Stress Course for Black Adolescents in Low-Income Communities: Examples of Surface Structure and Deep Structure Cultural Adaptations. Issue 4 (November 2022) - Clarke, Angela T.; Soto, Giemaly E.; Cook, Justin; Iloanusi, Chika; Akwarandu, Amarachi; Still Parris, Veronica
Highlights: Few evidence-based interventions have been culturally adapted for Black adolescents. A culturally adapted version of the evidence-based Coping With Stress Course shows promise. Surface structure and deep structure cultural adaptations are recommended. Abstract: Black adolescents in low-income communities are at increased risk of developing mental health problems due to the impact of cumulative poverty-related stressors and racial discrimination, yet Black youth have relatively low rates of mental health service utilization, resulting in significant unmet need. The Coping With Stress (CWS) Course is an evidence-based, cognitive behavioral intervention that has been shown to reduce the incidence of anxiety, mood, and conduct problems among predominantly White samples, as well as Asian and Latinx youth. In the past 25 years since the CWS Course was introduced, Black adolescents have either been severely underrepresented or conspicuously absent from program evaluation research on the CWS Course, with few exceptions. The purpose of this article is threefold: (1) to justify the need for cultural adaptations to the CWS Course for Black adolescents from low-income communities, (2) to describe the scientific basis for the specific surface structure and deep structure modifications made to the culturally adapted version of the CWS Course, known as Resilient In spite of Stressful Events or RISE, and (3) to illustrate the deep structure adaptations with a vignette drawn from implementation of the RISE program with Black adolescents in a low-income, urban community.